Improvement of wheat straw hydrolysis by cellulolytic blends of two Penicillium spp. (December 2016) - Saini, Jitendra Kumar; Singhania, Reeta Rani; Satlewal, Alok; Saini, Reetu; Gupta, Ravi; Tuli, Deepak; Mathur, Anshu; Adsul, Mukund
Abstract: Co-culture of fungal strains Penicillium janthinellum EMS-UV-8 (E), Penicillium funiculosum strain P (P) and Aspergillus sp. strain G (G) and blending of their crude cellulase were evaluated for improvements in cellulase activities as well as for enhanced hydrolysis of dilute acid pretreated wheat straw (PWS). The blending of crude enzymes of P and E enhanced the hydrolysis of PWS more effectively due to synergism in cellulolytic enzyme activities. Here, three types of blends were made on the basis of equal FPUs, equal protein content or fixed volume containing different proportions of individual enzymes, the former blend hydrolyzed 42.6% of PWS due to the 98%, 62%, 64% and 34% synergistic enhancement in endo-glucanase, cellulase (FPU), β-glucosidase and xylanase activities, respectively. Hydrolysis at 10% solid loading of PWS in roller bottle reactor with this blend further enhanced hydrolysis yield to 74% within 24 h, which was much better than the corresponding hydrolysis yields of individual (38.1% by E and 61.5% by P) or the commercial enzyme (62.3%). This study proved that synergistic blends of cellulases from two Penicillium spp. are cost-effective tools for efficient wheat straw hydrolysis for on-site biofuel production. Highlights: P . janthinellum and P . funiculosum crude enzymes used to make cellulase cocktail. First report on synergism between crude cellulases of two Penicillium strains. Endo–endo synergism in cellulase cocktails enhanced hydrolysis yield. 74% hydrolysis of pre-treated wheat straw by selected blend within 24 h. Roller bottle reactor enhanced hydrolysis by improved mixing at high solid loading.